A halogen-free copper-clad laminate substrate material containing flame-retardant modified benzoxazine resin and a preparation method thereof

By introducing flame retardant modified hyperbranched benzoxazine resin and modified magnesium hydroxide into the copper clad substrate material, a cross-linking network and a synergistic flame retardant structure is formed, the problem of insufficient flame retardant performance of existing materials is solved, and the efficient flame retardant and mechanical properties of the materials are improved.

CN119775716AActive Publication Date: 2025-04-08明光瑞智电子科技有限公司

Patent Information

Application Number
CN202510289734.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-08
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

The flame retardant performance of existing copper clad substrate materials is insufficient, and epoxy resins are flammable, making it difficult to meet the increasingly extensive technical development needs.

Method used

The flame-retardant modified hyperbranched benzooxazine resin is used to introduce flame-retardant modified hyperbranched benzooxazine resin and modified magnesium hydroxide into the epoxy resin to form a three-dimensional crosslinking network structure and an organic-inorganic collaborative flame retardant structure to improve the flame retardant and mechanical properties of the material.

Benefits of technology

The flame retardant and mechanical properties of copper clad substrate materials are significantly improved, the thermal stability and carbon-forming properties of the material are enhanced, and the higher technical needs are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775716A_ABST
    Figure CN119775716A_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of benzoxazine resins, and discloses a halogen-free copper-clad laminate substrate material containing flame-retardant modified benzoxazine resin and a preparation method thereof, wherein the present invention utilizes 1,2,4,5-benzenetetramine and phosphorus oxychloride to carry out chlorination reaction to obtain intermediate product 1, and then it is subjected to substitution reaction with p-hydroxybenzaldehyde to obtain intermediate product 2, and the aldehyde group contained therein is subjected to Schiff base reaction with 3-aminophenoxyphthalonitrile to obtain intermediate product 3, and under the catalytic reduction of Raney nickel, phosphorus-containing polyamine is obtained, and finally it is subjected to Manniene reaction with bisphenol A and polyformaldehyde to obtain a flame-retardant modified hyperbranched benzoxazine resin, and finally it is stirred and mixed evenly with E-51 epoxy resin, N, N-dimethylbenzylamine, etc., and coated on glass fiber cloth, and cured to obtain a halogen-free copper-clad laminate substrate material containing flame-retardant modified benzoxazine resin. The halogen-free copper-clad laminate substrate material prepared by the present invention has good flame retardancy, thermal stability and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of benzoxazine resins, in particular to a halogen-free copper clad laminate substrate material containing a flame retardant modified benzoxazine resin and a preparation method thereof. Background Art

[0002] Copper clad laminate is the basic material of electronic products. It is made of resin impregnated glue impregnated reinforcement material, covered with copper foil and hot pressed. Research on flame retardancy of copper clad laminate, which is indispensable for electronic products, is also crucial. Flame retardant modification of copper clad laminate usually adds flame retardant halogen to the resin matrix. However, halogen-containing compounds as flame retardants are easy to cause environmental pollution and endanger people's health. Therefore, the development of a halogen-free copper clad laminate substrate material is a hot topic of research.

[0003] Epoxy resin is widely used in the field of packaging materials for semiconductors, integrated circuits, copper-clad laminates and other electronic appliances. The limiting oxygen index of ordinary epoxy resin is only about 19.5, which is a flammable substance. Therefore, the copper-clad laminate substrate material prepared from it is potentially dangerous. How to improve the flame retardancy of epoxy resin to better meet the increasingly broad technological development needs has attracted widespread attention from researchers at home and abroad. Benzoxazine is a new type of resin prepared from phenolic compounds, polyformaldehyde and amine compounds. It is based on traditional phenolic resin and has good heat resistance, flame retardancy, dielectric properties and mechanical properties.

[0004] For example, the patent application publication number CN 103214794 A discloses a halogen-free epoxy resin composition for copper clad laminates and its application. The invention uses epoxy resin, benzoxazine, phenolic resin, etc. as raw materials, and the prepared composition has the characteristics of high heat resistance, low water absorption, good toughness, good adhesion, etc. However, it does not improve the flame retardant properties of the composite material. Summary of the invention

[0005] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a halogen-free copper clad laminate substrate material containing a flame retardant modified benzoxazine resin and a preparation method thereof. The prepared halogen-free copper clad laminate substrate material has good flame retardant properties and mechanical properties.

[0006] (II) Technical solution A halogen-free copper-clad laminate substrate material containing a flame-retardant modified benzoxazine resin, the halogen-free copper-clad laminate substrate material consisting of the following components in parts by weight: 100 parts by weight of E-51 epoxy resin, 20-50 parts by weight of a flame-retardant modified hyperbranched benzoxazine resin, 30-40 parts by weight of N,N-dimethylformamide, 30-40 parts by weight of methanol, 0.5-1 parts by weight of N,N-dimethylbenzylamine, and 12-30 parts by weight of modified magnesium hydroxide; The preparation method of the halogen-free copper clad laminate substrate material is as follows: E-51 epoxy resin, flame retardant modified hyperbranched benzoxazine resin, N,N-dimethylformamide and methanol are stirred and mixed evenly, N,N-dimethylbenzylamine is added thereto, and the mixture is aged at 80-90°C for 3-4h, and then modified magnesium hydroxide is added thereto, stirred and mixed evenly, and the mixture is coated on a glass fiber cloth, and cured under a curing process of 140°C / 3h+160°C / 2h+180°C / 3h to obtain a halogen-free copper clad laminate substrate material containing a flame retardant modified benzoxazine resin.

[0007] Preferably, the preparation method of the flame retardant modified hyperbranched benzoxazine resin is: (1) Add 1,2,4,5-benzenetetramine, dichloromethane and dichloroethane into a flask, stir evenly, then add phosphorus oxychloride, heat to 45-55°C, react for 3-6 hours, and after the reaction is completed, cool and filter, wash with acetonitrile, and dry to obtain intermediate 1; (2) Add the intermediate product 1 and acetonitrile into a flask, stir and mix at 60-70°C, introduce nitrogen, add p-hydroxybenzaldehyde and triethylamine, react at 80°C for 4-6 hours, and after the reaction, add a 1% by mass sodium hydroxide aqueous solution, stir for 20-30 minutes, wash with ice water and ether in turn, and dry to obtain the intermediate product 2; (3) Add the intermediate product 2,3-aminophenoxyphthalonitrile to a flask, add ethanol thereto, stir and mix evenly, then add glacial acetic acid thereto, stir and react at 55-65°C for 5-8h. After the reaction is completed, cool to room temperature, filter, wash with ethanol, and dry to obtain the intermediate product 3; (4) adding the intermediate product 3 and ethanol to a pressure autoclave, and then adding 30% by mass of ammonia water and Raney nickel thereto, reacting for 2-5 hours under a hydrogen pressure of 0.01 MPa. After the reaction is completed, filtering, desolventizing, dehydrating, and drying the filtrate to obtain a phosphorus-containing polyamine; (5) At room temperature, bisphenol A, phosphorus-containing polyamine and paraformaldehyde are dissolved in an ethanol solution, the temperature is raised to 70-85° C., and the reaction is carried out for 8-12 hours. After the reaction is completed, the solution is cooled to room temperature, filtered, washed with 5% sodium bicarbonate and deionized water in turn, and dried to obtain a flame-retardant modified hyperbranched benzoxazine resin.

[0008] More preferably, in (1), the molar ratio of 1,2,4,5-benzenetetramine to phosphorus oxychloride is 1:2-2.5, and the volume ratio of dichloromethane to dichloroethane is 1:1.

[0009] More preferably, in (2), the molar ratio of the intermediate product 1, p-hydroxybenzaldehyde and triethylamine is 1:2-2.5:4-6.

[0010] More preferably, in (3), the molar ratio of the intermediate product 2, 3-aminophenoxyphthalonitrile is 1:2-2.6.

[0011] Further preferably, in (4), the molar ratio of the intermediate product 3 to Raney nickel is 1:12-16.

[0012] More preferably, in (5), the molar ratio of bisphenol A, phosphorus-containing polyamine and paraformaldehyde is 1:0.5-0.8:4-6.

[0013] 3. Beneficial technical effects The present invention prepares a flame retardant modified hyperbranched benzoxazine resin having a plurality of branched structures, introduces the flame retardant modified hyperbranched benzoxazine resin into an epoxy resin, and utilizes the plurality of branched structures contained therein to form a three-dimensional cross-linked network structure. The cross-linked network contains a plurality of polar groups, which can generate hydrogen bonds with other polar groups in a substrate to form a plurality of cross-linking sites, thereby compensating for the poor mechanical properties of the epoxy resin, and synergistically improves the mechanical properties of the copper clad laminate substrate material with modified magnesium hydroxide; in addition, when the material is heated, the benzoxazine structure contained therein can open the ring to generate a hydroxyl group, which can catalyze the opening of the epoxy ring in the epoxy resin, generate more effective cross-linking with the epoxy resin, increase the cross-linking density, and improve the thermal stability and mechanical properties. The Schiff base structure therein can undergo a self-cross-linking reaction at high temperature due to the C=N functional group in its molecular structure to form a stable nitrogen-containing six-membered ring, thereby giving the material excellent carbon-forming performance, and further improving the mechanical properties and thermal stability of the material.

[0014] In addition, the hyperbranched benzoxazine resin prepared by the present invention contains a phosphorus-containing structure as an acid source, a large number of benzene ring structures as a carbon source, and a nitrogen-containing structure as a gas source, and the three synergistically improve the flame retardancy of the material; in addition, the surface of the modified magnesium hydroxide contained therein is connected with an organic group, which can be well wetted and dispersed in the substrate, and because magnesium hydroxide is a good inorganic flame retardant, an organic-inorganic synergistic flame retardant structure is formed, which jointly improves the flame retardancy of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is the reaction route of phosphorus-containing polyamines. DETAILED DESCRIPTION

[0016] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0017] The preparation method of 3-aminophenoxyphthalonitrile is as follows: 4-nitrophthalonitrile and 3-aminophenol are dissolved in a dimethyl sulfoxide solvent, potassium carbonate is added thereto, and the mixture is reacted at 80° C. for 10 hours under nitrogen protection. After the reaction is completed, 1M sodium hydroxide solution is added thereto, the mixture is filtered, washed with deionized water, and dried to obtain 3-aminophenoxyphthalonitrile.

[0018] Preparation method of modified magnesium hydroxide: add 10g of magnesium hydroxide to 100g of deionized water, stir and disperse, then add 0.8g of stearic acid, heat to 80°C, stir and react for 5h, after the reaction is completed, wash with deionized water, and dry to obtain modified magnesium hydroxide.

[0019] Preparation Example 1 (1) Under ice bath conditions, 0.2 mol of 1,2,4,5-benzenetetramine, 50 mL of dichloromethane, and 50 mL of dichloroethane were added to a flask and stirred evenly. Then, 0.4 mol of phosphorus oxychloride was added thereto, and the temperature was raised to 50°C. The reaction was allowed to proceed for 5 h. After the reaction was completed, the mixture was cooled and filtered, washed with acetonitrile, and dried to obtain intermediate 1.

[0020] (2) 0.04 mol of intermediate product 1 and 100 mL of acetonitrile were added to a flask, stirred and mixed at 65°C, nitrogen was introduced, 0.1 mol of p-hydroxybenzaldehyde and 0.2 mol of triethylamine were added thereto, and the reaction was carried out at 80°C for 5 h. After the reaction was completed, 1% by mass aqueous sodium hydroxide solution was added thereto, stirred for 30 min, and washed with ice water and ether in turn, and dried to obtain intermediate product 2.

[0021] (3) 0.05 mol of the intermediate product 2 and 0.1 mol of 3-aminophenoxyphthalonitrile were added to a flask, and 200 mL of ethanol was added thereto. The mixture was stirred and mixed evenly. Then, 5 drops of glacial acetic acid were dropped thereinto. The mixture was stirred and reacted at 60°C for 6 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain the intermediate product 3.

[0022] (4) 0.02 mol of the intermediate product 3 and 200 mL of ethanol were added to a pressure autoclave, and then 50 g of 30% by mass ammonia water and 0.25 mol of Raney nickel were added thereto. The reaction was carried out under a hydrogen pressure of 0.01 MPa for 4 h. After the reaction was completed, the filtrate was filtered, and the filtrate was decompressed, desolventized, dehydrated, and dried to obtain a phosphorus-containing polyamine.

[0023] (5) At room temperature, 0.04 mol of bisphenol A, 0.025 mol of phosphorus-containing polyamine, and 0.2 mol of polyformaldehyde were dissolved in 200 mL of ethanol solution, the temperature was raised to 70 °C, and the reaction was carried out for 8 h. After the reaction was completed, the solution was cooled to room temperature, filtered, washed with 5% sodium bicarbonate and deionized water in turn, and dried to obtain a flame-retardant modified hyperbranched benzoxazine resin.

[0024] (6) 100 g of E-51 epoxy resin, 20 g of flame retardant modified hyperbranched benzoxazine resin, 35 g of N,N-dimethylformamide and 40 g of methanol were stirred and mixed evenly, and then 0.5 g of N,N-dimethylbenzylamine was added thereto. The mixture was aged at 85°C for 4 h, and then 12 g of modified magnesium hydroxide was added thereto. The mixture was stirred and mixed evenly, and then coated on a glass fiber cloth. The mixture was cured at a curing process of 140°C / 3h+160°C / 2h+180°C / 3h to obtain a halogen-free copper clad laminate substrate material containing a flame retardant modified benzoxazine resin.

[0025] Preparation Example 2 (1) Under ice bath conditions, 0.2 mol of 1,2,4,5-benzenetetramine, 50 mL of dichloromethane, and 50 mL of dichloroethane were added to a flask and stirred evenly. Then, 0.5 mol of phosphorus oxychloride was added and the temperature was raised to 55°C. The reaction was allowed to proceed for 4 h. After the reaction was completed, the mixture was cooled and filtered, washed with acetonitrile, and dried to obtain intermediate 1.

[0026] (2) 0.04 mol of intermediate product 1 and 100 mL of acetonitrile were added to a flask, stirred and mixed at 70°C, nitrogen was introduced, 0.08 mol of p-hydroxybenzaldehyde and 0.24 mol of triethylamine were added thereto, and the reaction was carried out at 80°C for 6 h. After the reaction was completed, 1% by mass aqueous sodium hydroxide solution was added thereto, stirred for 20 min, and washed with ice water and ether in turn, and dried to obtain intermediate product 2.

[0027] (3) 0.05 mol of the intermediate product 2 and 0.12 mol of 3-aminophenoxyphthalonitrile were added to a flask, and 200 mL of ethanol was added thereto. The mixture was stirred and mixed evenly. Then 4 drops of glacial acetic acid were dropped thereinto. The mixture was stirred and reacted at 65°C for 6 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain the intermediate product 3.

[0028] (4) 0.02 mol of the intermediate product 3 and 200 mL of ethanol were added to a pressure autoclave, and then 50 g of 30% by mass ammonia water and 0.3 mol of Raney nickel were added thereto. The reaction was carried out under a hydrogen pressure of 0.01 MPa for 4 h. After the reaction was completed, the filtrate was filtered, and the filtrate was decompressed, desolventized, dehydrated, and dried to obtain a phosphorus-containing polyamine.

[0029] (5) At room temperature, 0.04 mol of bisphenol A, 0.032 mol of phosphorus-containing polyamine, and 0.16 mol of polyformaldehyde were dissolved in 200 mL of ethanol solution, and the temperature was raised to 75 °C. The reaction was allowed to proceed for 10 h. After the reaction was completed, the solution was cooled to room temperature, filtered, washed with 5% sodium bicarbonate and deionized water, and dried to obtain a flame-retardant modified hyperbranched benzoxazine resin.

[0030] (6) 100 g of E-51 epoxy resin, 25 g of flame retardant modified hyperbranched benzoxazine resin, 30 g of N,N-dimethylformamide and 30 g of methanol were stirred and mixed evenly, and then 0.6 g of N,N-dimethylbenzylamine was added thereto. The mixture was aged at 80°C for 4 h, and then 15 g of modified magnesium hydroxide was added thereto. The mixture was stirred and mixed evenly, and then coated on a glass fiber cloth. The mixture was cured at a curing process of 140°C / 3h+160°C / 2h+180°C / 3h to obtain a halogen-free copper clad laminate substrate material containing a flame retardant modified benzoxazine resin.

[0031] Preparation Example 3 (1) Under ice bath conditions, 0.2 mol of 1,2,4,5-benzenetetramine, 50 mL of dichloromethane, and 50 mL of dichloroethane were added to a flask and stirred evenly. Then, 0.45 mol of phosphorus oxychloride was added, the temperature was raised to 45°C, and the reaction was carried out for 6 h. After the reaction was completed, the mixture was cooled and filtered, washed with acetonitrile, and dried to obtain intermediate 1.

[0032] (2) 0.04 mol of intermediate product 1 and 100 mL of acetonitrile were added to a flask, stirred and mixed at 60°C, nitrogen was introduced, 0.09 mol of p-hydroxybenzaldehyde and 0.16 mol of triethylamine were added thereto, and the mixture was reacted at 80°C for 4 h. After the reaction was completed, 1% by mass aqueous sodium hydroxide solution was added thereto, stirred for 25 min, and washed with ice water and ether in turn, and dried to obtain intermediate product 2.

[0033] (3) 0.05 mol of the intermediate product 2 and 0.1 mol of 3-aminophenoxyphthalonitrile were added to a flask, and 200 mL of ethanol was added thereto. The mixture was stirred and mixed evenly. Then, 5 drops of glacial acetic acid were dropped thereinto. The mixture was stirred and reacted at 60°C for 6 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain the intermediate product 3.

[0034] (4) 0.02 mol of the intermediate product 3 and 200 mL of ethanol were added to a pressure autoclave, and then 50 g of 30% by mass ammonia water and 0.32 mol of Raney nickel were added thereto. The reaction was carried out under a hydrogen pressure of 0.01 MPa for 5 h. After the reaction was completed, the filtrate was filtered, and the filtrate was decompressed, desolventized, dehydrated, and dried to obtain a phosphorus-containing polyamine.

[0035] (5) At room temperature, 0.04 mol of bisphenol A, 0.02 mol of phosphorus-containing polyamine, and 0.24 mol of polyformaldehyde were dissolved in 200 mL of ethanol solution, and the temperature was raised to 85 °C. The reaction was allowed to proceed for 12 h. After the reaction was completed, the solution was cooled to room temperature, filtered, washed with 5% sodium bicarbonate and deionized water, and dried to obtain a flame-retardant modified hyperbranched benzoxazine resin.

[0036] (6) 100 g of E-51 epoxy resin, 35 g of flame retardant modified hyperbranched benzoxazine resin, 40 g of N,N-dimethylformamide and 35 g of methanol were stirred and mixed evenly, and then 1 g of N,N-dimethylbenzylamine was added thereto. The mixture was aged at 90°C for 3 h, and then 20 g of modified magnesium hydroxide was added thereto. The mixture was stirred and mixed evenly, and then coated on a glass fiber cloth. The mixture was cured at a curing process of 140°C / 3h+160°C / 2h+180°C / 3h to obtain a halogen-free copper clad laminate substrate material containing a flame retardant modified benzoxazine resin.

[0037] Preparation Example 4 (1) Under ice bath conditions, 0.2 mol of 1,2,4,5-benzenetetramine, 50 mL of dichloromethane, and 50 mL of dichloroethane were added to a flask and stirred evenly. Then, 0.42 mol of phosphorus oxychloride was added and the temperature was raised to 50°C. The reaction was allowed to proceed for 3 h. After the reaction was completed, the mixture was cooled and filtered, washed with acetonitrile, and dried to obtain intermediate 1.

[0038] (2) 0.04 mol of intermediate product 1 and 100 mL of acetonitrile were added to a flask, stirred and mixed at 65°C, nitrogen was introduced, 0.09 mol of p-hydroxybenzaldehyde and 0.2 mol of triethylamine were added thereto, and the reaction was carried out at 80°C for 5 h. After the reaction was completed, 1% by mass aqueous sodium hydroxide solution was added thereto, stirred for 25 min, and washed with ice water and ether in turn, and dried to obtain intermediate product 2.

[0039] (3) 0.05 mol of intermediate product 2 and 0.12 mol of 3-aminophenoxyphthalonitrile were added to a flask, and 200 mL of ethanol was added thereto. The mixture was stirred and mixed evenly. Then, 3 drops of glacial acetic acid were dropped thereinto. The mixture was stirred and reacted at 65°C for 5 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain intermediate product 3.

[0040] (4) 0.02 mol of the intermediate product 3 and 200 mL of ethanol were added to a pressure autoclave, and then 50 g of 30% by mass ammonia water and 0.3 mol of Raney nickel were added thereto. The reaction was carried out under a hydrogen pressure of 0.01 MPa for 2 h. After the reaction was completed, the filtrate was filtered, and the filtrate was decompressed, desolventized, dehydrated, and dried to obtain a phosphorus-containing polyamine.

[0041] (5) At room temperature, 0.04 mol of bisphenol A, 0.02 mol of phosphorus-containing polyamine, and 0.2 mol of polyformaldehyde were dissolved in 200 mL of ethanol solution, and the temperature was raised to 75 °C. The reaction was allowed to proceed for 10 h. After the reaction was completed, the solution was cooled to room temperature, filtered, washed with 5% sodium bicarbonate and deionized water, and dried to obtain a flame-retardant modified hyperbranched benzoxazine resin.

[0042] (6) 100 g of E-51 epoxy resin, 40 g of flame retardant modified hyperbranched benzoxazine resin, 35 g of N,N-dimethylformamide and 40 g of methanol were stirred and mixed evenly, and then 0.8 g of N,N-dimethylbenzylamine was added thereto. The mixture was aged at 85°C for 4 h, and then 25 g of modified magnesium hydroxide was added thereto. The mixture was stirred and mixed evenly, and then coated on a glass fiber cloth. The mixture was cured at a curing process of 140°C / 3h+160°C / 2h+180°C / 3h to obtain a halogen-free copper clad laminate substrate material containing a flame retardant modified benzoxazine resin.

[0043] Preparation Example 5 (1) Under ice bath conditions, 0.2 mol of 1,2,4,5-benzenetetramine, 50 mL of dichloromethane, and 50 mL of dichloroethane were added to a flask and stirred evenly. Then, 0.45 mol of phosphorus oxychloride was added and the temperature was raised to 55°C. The reaction was allowed to proceed for 5 h. After the reaction was completed, the mixture was cooled and filtered, washed with acetonitrile, and dried to obtain intermediate 1.

[0044] (2) 0.04 mol of intermediate product 1 and 100 mL of acetonitrile were added to a flask, stirred and mixed at 65°C, nitrogen was introduced, 0.09 mol of p-hydroxybenzaldehyde and 0.22 mol of triethylamine were added thereto, and the reaction was carried out at 80°C for 6 h. After the reaction was completed, 1% by mass aqueous sodium hydroxide solution was added thereto, stirred for 25 min, and washed with ice water and ether in turn, and dried to obtain intermediate product 2.

[0045] (3) 0.05 mol of the intermediate product 2 and 0.13 mol of 3-aminophenoxyphthalonitrile were added to a flask, and 200 mL of ethanol was added thereto. The mixture was stirred and mixed evenly. Then 4 drops of glacial acetic acid were dropped thereinto. The mixture was stirred and reacted at 55°C for 8 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with ethanol, and dried to obtain the intermediate product 3.

[0046] (4) 0.02 mol of the intermediate product 3 and 200 mL of ethanol were added to a pressure autoclave, and then 50 g of 30% by mass ammonia water and 0.24 mol of Raney nickel were added thereto. The reaction was carried out under a hydrogen pressure of 0.01 MPa for 4 h. After the reaction was completed, the filtrate was filtered, and the filtrate was decompressed, desolventized, dehydrated, and dried to obtain a phosphorus-containing polyamine.

[0047] (5) At room temperature, 0.04 mol of bisphenol A, 0.03 mol of phosphorus-containing polyamine, and 0.2 mol of polyformaldehyde were dissolved in 200 mL of ethanol solution, and the temperature was raised to 75 °C. The reaction was allowed to proceed for 12 h. After the reaction was completed, the solution was cooled to room temperature, filtered, washed with 5% sodium bicarbonate and deionized water, and dried to obtain a flame-retardant modified hyperbranched benzoxazine resin.

[0048] (6) 100 g of E-51 epoxy resin, 50 g of flame retardant modified hyperbranched benzoxazine resin, 35 g of N,N-dimethylformamide and 40 g of methanol were stirred and mixed evenly, and then 0.8 g of N,N-dimethylbenzylamine was added thereto. The mixture was aged at 85°C for 4 h, and then 30 g of modified magnesium hydroxide was added thereto. The mixture was stirred and mixed evenly, and then coated on a glass fiber cloth. The mixture was cured at a curing process of 140°C / 3h+160°C / 2h+180°C / 3h to obtain a halogen-free copper clad laminate substrate material containing a flame retardant modified benzoxazine resin.

[0049] Comparative Example 1 The difference between this comparative example and preparation example 1 is that in step (6), no flame retardant modified hyperbranched benzoxazine resin is contained.

[0050] The glass transition temperature of the material was tested using a thermal analyzer. In a nitrogen atmosphere, the heating rate was 20°C / min and the temperature range was 25-300°C.

[0051] Table 1:

[0052] It can be seen from the table that the copper clad laminate substrate material prepared by the present invention has good thermal stability.

[0053] Refer to GB / T2406-2008 and use an oxygen index tester to test the flame retardant properties of the material.

[0054] Table 2:

[0055] The higher the oxygen index, the higher the flame retardant performance. It can be seen from the table that the copper clad laminate substrate material prepared by the present invention has good flame retardant performance.

[0056] Refer to GB / T4722-2017 and use an electronic universal testing machine to test the mechanical properties of the material.

[0057] Table 3:

[0058] It can be seen from the table that the copper clad laminate substrate material prepared by the present invention has good mechanical properties, and the maximum bending strength can reach 521.7 MPa.

[0059] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.

Claims

1. A halogen-free copper-clad laminate substrate material containing a flame-retardant modified benzoxazine resin, characterized in that: The halogen-free copper clad laminate substrate material is composed of the following components in parts by weight: 100 parts by weight of E-51 epoxy resin, 20-50 parts by weight of flame retardant modified hyperbranched benzoxazine resin, 30-40 parts by weight of N,N-dimethylformamide, 30-40 parts by weight of methanol, 0.5-1 parts by weight of N,N-dimethylbenzylamine, and 12-30 parts by weight of modified magnesium hydroxide; The preparation method of the halogen-free copper clad laminate substrate material is as follows: E-51 epoxy resin, flame retardant modified hyperbranched benzoxazine resin, N,N-dimethylformamide and methanol are stirred and mixed evenly, N,N-dimethylbenzylamine is added thereto, and the mixture is aged at 80-90°C for 3-4h, and then modified magnesium hydroxide is added thereto, stirred and mixed evenly, and the mixture is coated on a glass fiber cloth, and cured under a curing process of 140°C / 3h+160°C / 2h+180°C / 3h to obtain a halogen-free copper clad laminate substrate material containing a flame retardant modified benzoxazine resin.

2. The halogen-free copper clad laminate substrate material containing flame retardant modified benzoxazine resin according to claim 1, characterized in that: The preparation method of the flame retardant modified hyperbranched benzoxazine resin is: (1) Add 1,2,4,5-benzenetetramine, dichloromethane and dichloroethane into a flask, stir evenly, then add phosphorus oxychloride, heat to 45-55°C, react for 3-6 hours, and after the reaction is completed, cool and filter, wash with acetonitrile, and dry to obtain intermediate 1; (2) Add the intermediate product 1 and acetonitrile into a flask, stir and mix at 60-70°C, introduce nitrogen, add p-hydroxybenzaldehyde and triethylamine, react at 80°C for 4-6 hours, and after the reaction, add a 1% by mass sodium hydroxide aqueous solution, stir for 20-30 minutes, wash with ice water and ether in turn, and dry to obtain the intermediate product 2; (3) Add the intermediate product 2,3-aminophenoxyphthalonitrile to a flask, add ethanol thereto, stir and mix evenly, then add glacial acetic acid thereto, stir and react at 55-65°C for 5-8h. After the reaction is completed, cool to room temperature, filter, wash with ethanol, and dry to obtain the intermediate product 3; (4) adding the intermediate product 3 and ethanol to a pressure autoclave, and then adding 30% by mass of ammonia water and Raney nickel thereto, reacting for 2-5 hours under a hydrogen pressure of 0.01 MPa. After the reaction is completed, filtering, desolventizing, dehydrating, and drying the filtrate to obtain a phosphorus-containing polyamine; (5) At room temperature, bisphenol A, phosphorus-containing polyamine and paraformaldehyde are dissolved in an ethanol solution, the temperature is raised to 70-85° C., and the reaction is carried out for 8-12 hours. After the reaction is completed, the solution is cooled to room temperature, filtered, washed with 5% sodium bicarbonate and deionized water in turn, and dried to obtain a flame-retardant modified hyperbranched benzoxazine resin.

3. The halogen-free copper clad laminate substrate material containing flame retardant modified benzoxazine resin according to claim 2, characterized in that: In the above (1), the molar ratio of 1,2,4,5-benzenetetramine to phosphorus oxychloride is 1:2-2.

5.

4. The halogen-free copper clad laminate substrate material containing flame retardant modified benzoxazine resin according to claim 2, characterized in that: In the above (2), the molar ratio of the intermediate product 1, p-hydroxybenzaldehyde and triethylamine is 1:2-2.5:4-6.

5. The halogen-free copper clad laminate substrate material containing flame retardant modified benzoxazine resin according to claim 2, characterized in that: In the above (3), the molar ratio of the intermediate product 2, 3-aminophenoxyphthalonitrile is 1:2-2.

6.

6. The halogen-free copper clad laminate substrate material containing flame retardant modified benzoxazine resin according to claim 2, characterized in that: In the above (4), the molar ratio of the intermediate product 3 to Raney nickel is 1:12-16.

7. The halogen-free copper clad laminate substrate material containing flame retardant modified benzoxazine resin according to claim 2, characterized in that: In the above (5), the molar ratio of bisphenol A, phosphorus-containing polyamine and paraformaldehyde is 1:0.5-0.8:4-6.

Citation Information

Patent Citations

  • Halogen-free epoxy resin composition for copper-clad plate and application thereof

    CN103214794A

  • OLED (Organic Light Emission Diode) material, application and device

    CN106083861A

  • Fire-retardant composition, curing agent, and phenol-based epoxy resin

    CN106916281A

  • Preparation method of complete biogenetic derivation benzoxazine resin and application thereof

    CN109180889A

  • Preparation method of basalt fiber reinforced fireproof flame-retardant polymer-based composite material

    CN117384111A

Cited By

  • Wear-resistant heat-insulating coating and preparation method thereof

    CN121699492A

  • A wear-resistant and heat-insulating coating and its preparation method

    CN121699492B